Connecting the fragmented Forests by Opportunity of Vertical dual Land use-III (Analysis along the length of RoW of Transmission Lines) - Misra, Vinay Kant (Indian Forester, 2025)
Plantation of dwarf species (preferably medicinal plants) in right of way (RoW) of transmission lines is a unique mandatory condition in the projects of forest land diversion for transmission lines under Forest (Conservation) Act, 1980; now named as Van (Sanrakshan evam Samvardhan) Adhiniyam, 1980. It provides a unique opportunity of vertical dual land use by differentiating the vertical space above land for different uses. In part-I and II of the present study, various aspects of the existing practices including safety, species selection, spacing of seedlings, phytoclimatic zones and vegetation types were given based on review of 1080 projects of forest land diversion for transmission lines. Cross-sectional analysis of RoW of transmission lines of different voltage levels was made to find out the available vertical space. The method of calculation of horizontal space (Kvalue) for relatively taller (T-value) dwarf plants was also given along with differential height model of plantation. A list of 250 perennial dwarf species of different phytoclimatic zones of India was given along with their distribution, local names, available propagation techniques and palatability/edibility for wildlife. The detailed plan of plantation of dwarf species including lay-out, cost analysis, rate of levy demand and method to calculate levy for future years was also given in part-II of this study. The bamboo fencing was proposed for forest areas in place of present common practice of barbedwire fencing along with comparison of costs of different types of prevailing fencing practices. In present part-III of this study, the comparison of various guidelines of MoEF&CC and CEA issued in 2023 is made with those of earlier guidelines/regulations to update the outcomes of study. Views on further amendment of guidelines/regulations to reconsideration of available vertical space for dwarf plants were given to utilize the unused vertical space at safe distance (vertical clearance) in place of distance from maximum sag point.